2021
DOI: 10.1029/2020gl090963
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Integrated Kinetic Energy in an Ensemble of HighResMIP Simulations

Abstract: This study investigates tropical cyclone integrated kinetic energy, a measure which takes into account the intensity and the size of the storms and which is closely associated with their damage potential, in three different global climate models integrated following the HighResMIP protocol. In particular, the impact of horizontal resolution and of the ocean coupling are assessed. We find that, while the increase in resolution results in smaller and more intense storms, the integrated kinetic energy of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
(95 reference statements)
1
12
0
Order By: Relevance
“…Due to this lack of significant change in TC size, TC IKE on average remains the same level, which indicates a stabilization of TC destructive potential at LMI, even though the LMI has increased significant during this period. This stabilization, due to the large dependence of IKE on TC size 16 , 17 , 43 , would seem to support the climate model simulations which show projected increase in TC intensity but no change in TC integrated kinetic energy 18 . Interestingly, a recent study 9 also reported no recent change in the acumulated cyclone energy of major TCs.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Due to this lack of significant change in TC size, TC IKE on average remains the same level, which indicates a stabilization of TC destructive potential at LMI, even though the LMI has increased significant during this period. This stabilization, due to the large dependence of IKE on TC size 16 , 17 , 43 , would seem to support the climate model simulations which show projected increase in TC intensity but no change in TC integrated kinetic energy 18 . Interestingly, a recent study 9 also reported no recent change in the acumulated cyclone energy of major TCs.…”
Section: Discussionsupporting
confidence: 68%
“…The maximum wind speed, the latitude of TC center and R 18 are used as three inputs of the analytic wind profile model. This procedure for wind field reconstruction has been fully validated 43 and applied with global climate model simulations 18 . To examine the robustness of IKE calculation, we also apply an alternative wind profile model—the updated Holland model 25 that also requires the radius of maximum wind which is obtained from the IBTrACS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation on the TC destructive potential was conducted via computing Integrated Kinetic Energy (IKE) (Powell & Reinhold, 2007) which considers the entirety of a TC's surface wind field following Kreussler et al. (2021): IKE=vρU220.17emdV=12kgm2×AU20.17emdA $IKE={\int }_{v}\frac{\rho {U}^{2}}{2}\,dV=\frac{1}{2}kg{m}^{-2}\times {\int }_{A}{U}^{2}\,dA$ where the air density is uniformly equal 1 kg m − 3 , and U is 10‐m wind speed exceeding 25 kts at grid points within 1,000 km of the TC center. The 25‐kt threshold was chosen to include weak TCs in the IKE assessment.…”
Section: Data Methodology and Experimental Designmentioning
confidence: 99%
“…High‐resolution climate models outperform their coarse‐resolution counterparts. They generate more realistic representations of many aspects of the Earth's system, including the spatial distribution and frequency of tropical cyclones, finer‐scale air‐sea fluxes, heat transports of boundary currents, the Atlantic meridional overturning circulation, as well as weather extremes at regional scales (Bellucci et al., 2021; Docquier et al., 2019; Hewitt et al., 2020; Koenigk et al., 2021; Kreussler et al., 2021; M. J. Roberts et al., 2018, 2020; Small et al., 2019; Wengel et al., 2021). However, the impact of climate model resolution on ENSO simulations is yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%